2016
DOI: 10.1002/biot.201600454
|View full text |Cite
|
Sign up to set email alerts
|

A simplified procedure for antibody engineering by yeast surface display: Coupling display levels and target binding by ribosomal skipping

Abstract: Yeast surface display is a valuable, widely used method for protein engineering. However, current yeast display applications rely on the staining of epitope tags in order to verify full-length presentation of the protein of interest on the cell surface. We aimed at developing a modified yeast display approach that relies on ribosomal skipping, thereby enabling the translation of two proteins from one open reading frame and, in that manner, generating an intracellular fluorescence signal. This improved setup is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Simultaneous expression of heavy- and light-chains is enabled via the introduction of the picornaviral 2A peptide, mediating ribosomal skipping and therefore the lack of peptide bond formation between Aga2p which is fused to the heavy chain and the light chain. In contrast to internal ribosome entry sites, ribosomal skipping results in the translation of equal amounts of each protein and it has been shown previously that the 2A peptide is a versatile tool for yeast surface display [ 21 , 33 ]. Similarly to the two-directional display system, signature sequences were constituents of sequence-encoding antibody constant regions or signal sequences and Bsa I sites were designed to be removed during restriction-ligation reaction, allowing for seamless one-step cloning of the final library display vector (pExp_bicis).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous expression of heavy- and light-chains is enabled via the introduction of the picornaviral 2A peptide, mediating ribosomal skipping and therefore the lack of peptide bond formation between Aga2p which is fused to the heavy chain and the light chain. In contrast to internal ribosome entry sites, ribosomal skipping results in the translation of equal amounts of each protein and it has been shown previously that the 2A peptide is a versatile tool for yeast surface display [ 21 , 33 ]. Similarly to the two-directional display system, signature sequences were constituents of sequence-encoding antibody constant regions or signal sequences and Bsa I sites were designed to be removed during restriction-ligation reaction, allowing for seamless one-step cloning of the final library display vector (pExp_bicis).…”
Section: Resultsmentioning
confidence: 99%
“…In the bicistronic system (bicis), Fab display is mediated by ribosomal skipping (Fig. 1 b) [ 21 , 22 ]. We show that large antibody libraries with more than 10 8 unique clones can readily be constructed by applying the herein presented approach.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid both possible steric hindrance by secondary fluorescence antibody, and the time-consuming and expensive tagging process of yeast expression, we decided to use an alternative yeast display construct in which a T2A-EGFP sequence fused to the C terminus of the displayed protein allows intracellular EGFP expression to be correlated with display level of the surface proteins ( Fig. 2B) (19). We observed that the EGFP expression level indicates a similar expression profile for PcTx1.…”
Section: Resultsmentioning
confidence: 99%
“…Ribosomal skipping (T2A peptide) results in the secretion of the mIL-3 protein, carrying a secretion signal (app8 31 ) www.nature.com/scientificreports www.nature.com/scientificreports/ (Supplementary Table S1). Simultaneously, mCherry fluorescent protein accumulates intracellularly in a correlation to the expression rate of the cytokine, as demonstrated by Grzeschik et al 32 , and thus serves as an expression control.…”
Section: Activation Of Ba/f3-cis-d2egfp Reporter Cells Using Mil-3 Comentioning
confidence: 85%